Penerapan Model Pembelajaran Kolaboratif untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa di Kelas IV MIS Nurul Yaqin Muaro Jambi - Musyaffa, Musyaffa; Ajrina, Titin Titin Rahma (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2025)
For kids to be ready to compete at the next level of education, they must develop their creative thinking skills starting in elementary school. But in practice, MIS Nurul Yaqin Muaro Jambi's creative thinking abilities are still rated as low. Applying a collaborative learning model is one way to help students develop their creative thinking abilities because it requires them to work as a team and participate in a study group that has been formed so that they can share ideas or opinions with their peers. The four-stage Kemmis McTagger model is used in this investigation. Enhancing the creative thinking abilities of Mis Nuru Yaqin Muaro Jambi's grade IV students is the aim of this project. In cycle II, teacher activity improved to 92% with very good credentials, compared to 78% in cycle I, which was based on observations of teacher activities. Observations of student activities throughout cycle I yielded results with a 69.77% percentage. With good qualifications, it then rose to 80.68% in cycle II. These findings indicate a rise in the use of collaborative learning models by both teachers and students. Therefore, it can be said that class IV MIS Nurul Yaqin Muaro Jambi students' creative thinking abilities can be enhanced through the use of collaborative learning models.